1990
DOI: 10.1021/bi00457a013
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemistry of leukotriene B4 metabolites formed by the reductase pathway in porcine polymorphonuclear leukocytes: inversion of stereochemistry of the 12-hydroxyl group

Abstract: Leukotriene B4 (LTB4), a potent proinflammatory agent, is a major metabolite of arachidonic acid in polymorphonuclear leukocytes (PMNL). When porcine PMNL were incubated with LTB4 and the products purified by reversed-phase high-pressure liquid chromatography (HPLC), we previously identified two metabolites: 10,11-dihydro-LTB4 and 10,11-dihydro-12-oxo-LTB4 [Powell, W. S., & Gravelle, F. (1989) J. Biol. Chem. 264, 5364-5369]. Further analysis of the reaction products by normal-phase HPLC has now revealed the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…We have previously reported that porcine PMNL convert LTB4 to 10,1 l-dihydro-LTB4,10,11-dihydro-12-epi-LTB4, and 10.11dihydro-12-oxo-LTB4 (Powell & Gravelle, 1989;Wainwright et al, 1990). 10,11-Dihydro-12-epi-LTB4 was not an initial product but was formed after a lag period, presumably from either 10,11-dihydro-LTB4 or 10,11-dihydro-12-oxo-LTB4 (Wainwright et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously reported that porcine PMNL convert LTB4 to 10,1 l-dihydro-LTB4,10,11-dihydro-12-epi-LTB4, and 10.11dihydro-12-oxo-LTB4 (Powell & Gravelle, 1989;Wainwright et al, 1990). 10,11-Dihydro-12-epi-LTB4 was not an initial product but was formed after a lag period, presumably from either 10,11-dihydro-LTB4 or 10,11-dihydro-12-oxo-LTB4 (Wainwright et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that porcine PMNL convert LTB4 to 10,1 l-dihydro-LTB4,10,11-dihydro-12-epi-LTB4, and 10.11dihydro-12-oxo-LTB4 (Powell & Gravelle, 1989;Wainwright et al, 1990). 10,11-Dihydro-12-epi-LTB4 was not an initial product but was formed after a lag period, presumably from either 10,11-dihydro-LTB4 or 10,11-dihydro-12-oxo-LTB4 (Wainwright et al, 1990). We have now shown that 12(5)-HETE is metabolized by porcine PMNL in a similar manner, giving 12(R)-hydroxy-5,8,14-eicosatrienoic acid, 12(5)-hydroxy-5,8,14-eicosatrienoic acid, and 12-oxo-5,8,l4-eicosatrienoic acid, which were identified by mass spectrometry and NMR spectroscopy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, one of the intriguing possibilities with respect to the physiological role of DHRS9 might be its participation in the so-called 12-hydroxyeicosanoid dehydrogenase/10,11-reductase pathway, which was implicated in metabolism of 12( S )-HETE, LTB 4 , and possibly of 13( S )-HODE ( 44 , 45 ). Pioneering studies carried out by Wainwright and Powell demonstrated that catabolic conversion of 12( S )-HETE and LTB 4 is initiated when both compounds are rapidly oxidized by 12-hydroxyeicosanoid dehydrogenase followed by reduction of the 10,11-double bond by 10,11-reductase ( 44 ).…”
Section: Discussionmentioning
confidence: 99%